2017
DOI: 10.1098/rspb.2017.1491
|View full text |Cite
|
Sign up to set email alerts
|

Parasite infection induces size-dependent host dispersal: consequences for parasite persistence

Abstract: Host dispersal is now recognized as a key predictor of the landscape-level persistence and expansion of parasites. However, current theories treat post-infection dispersal propensities as a fixed trait, and the plastic nature of host's responses to parasite infection has long been underappreciated. Here, we present a mark-recapture experiment in a single host-parasite system (larval parasites of the freshwater mussel and its salmonid fish host) and provide, to our knowledge, the first empirical evidence that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…These are a common dataset obtained through a mark-recapture study, so no additional work may be required to use the DOCM. Furthermore, if users have an independent estimate of detection probability ξ through multiple-pass removal (Dorazio et al 2005) or other methods, it is also possible to estimate the true survival rate s that is corrected for permanent emigration (Terui et al 2017). However, there are caveats when interpreting the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are a common dataset obtained through a mark-recapture study, so no additional work may be required to use the DOCM. Furthermore, if users have an independent estimate of detection probability ξ through multiple-pass removal (Dorazio et al 2005) or other methods, it is also possible to estimate the true survival rate s that is corrected for permanent emigration (Terui et al 2017). However, there are caveats when interpreting the results.…”
Section: Resultsmentioning
confidence: 99%
“…Ecologists have been intrigued by the spatial process due to its implications for critical applied issues, such as the metapopulation persistence of endangered species in fragmented landscapes (Hanski 1999). More recently, accumulating evidence suggests that dispersal is highly plastic and context-dependent with significant consequences for landscape-level dynamics (Bonte & de la Pena 2009; Bonte et al 2012; Cote et al 2011; Cote et al 2013; Fronhofer et al 2018; Fronhofer et al 2017; Little et al 2019; Terui et al 2017). For example, Fronhofer et al (2018) have shown that context-dependent dispersal in experimental landscapes has stabilizing effects on local food webs coupled via dispersal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, stream-dwelling fishes serve as an excellent model system to measure the dispersal distance of individuals (e.g. Pépino, Rodríguez, & Magnan, 2012;Terui, Ooue, Urabe, & Nakamura, 2017), which should be an indication of their gene flow potential. Because stream fishes generally move linearly along the stream, we can easily measure the distance each individual travels by contiguously established study sections.…”
Section: Introductionmentioning
confidence: 99%
“…number of offspring that survive to juvenile) which had been estimated in our previous study (Fukui et al, 2018). Although dispersal distance is not necessarily equivalent to gene flow, it should be an available indicator for the spread of non-native genes (Pépino et al, 2012;Terui et al, 2017). identified to species level based on appearance (Nakabo, 2000), and fork length measured (nearest mm).…”
Section: Introductionmentioning
confidence: 99%